Factors Influencing the Human Development Index in Indonesia Using Structural Equation Modeling-Partial Least Square - Rifki Saefullah; Besse Arnawisuda Ningsi (International Journal of Business, Economics, and Social Development, 2025)
HDI is a benchmark for a country in achieving human development in the country. Indonesia is a developing country with a relatively increasing HDI value every year. This shows that the efforts made by Indonesia are going well. However, Indonesia experienced a decrease in HDI value in 2019 towards 2020, due to restrictions on activities caused by the Covid-19 pandemic. In addition, the HDI value in each province in Indonesia is uneven, even from the publication data of the Central Statistics Agency (BPS) shows a significant difference in HDI value between provinces in Indonesia. So that evaluation and improvement are needed to be able to equalize and stabilize HDI in Indonesia. HDI value can be influenced by several factors including economy, education, and health. This study aims to determine the direct effect of economic variables on HDI, the direct effect of education variables on HDI, the direct effect of health variables on HDI, the indirect effect of education variables on HDI through economic variables and health variables. The data used in this study are data on the Human Development Index of economic, education and health variables along with the indicators that measure them, from 34 provinces in Indonesia in 2022. This study applies SEM-PLS to determine the factors that influence the Human Development Index (HDI). The results of this study indicate that economic variables and education variables have a direct influence on the Human Development Index (HDI), while health variables have no direct influence on the Human Development Index (HDI). Then the education variable through the economic variable has an indirect effect on the Human Development Index (HDI), and the education variable through the health variable has no indirect effect on the Human Development Index (HDI).